Listeriosis Phytotherapy: A Review Study on the Effectiveness of Iranian Medicinal Plants in Treatment of Listeriosis. (April 2017) - Rafieian-Kopaei, Mahmoud; Saki, Kourosh; Bahmani, Mahmoud; Ghafourian, Sobhan; Sadeghifard, Nourkhoda; Taherikalani, Morovat
Listeria monocytogenes can be found in many processed foods, raw milk, dairy products, meat and meat products such as sausages, beef and fish products, seafoods, eggs, fruits, and vegetables such as radish and cabbage. This article is a review study on the Iranian medicinal plants applied for treatment of listeriosis. Information of this review article was obtained by searching various key words such as Listeria monocytogenes, medicinal plants, plant extracts and essential oils among scientific articles published in databases of Google scholar, ISI Web of Knowledge, PubMed, Scopus, SID and Magiran. Thyme, German chamomile, great chamomile, yarrow, onion, oregano, nutmeg, sage, sagebrush, hyssop, rosemary, St John's wort, safflower, ajowan, cumin, peppermint, shallot, anise, and parsnip are known antilisteriosis medicinal plants. Bioactive phytochemicals, antioxidants and monoterpenes, sesquiterpene, coumarin, flavonoids, tannins, saponins, alkaloids, and terpenoids are the main ingredients of antilisteriosis medicinal plants.